2017
DOI: 10.1016/j.jtcvs.2017.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin inhibitors lower pulmonary vascular resistance and improve functional capacity in patients with Fontan circulation

Abstract: This is the first study that assesses by cardiac catheterization and CPET the effects of ERA in patients with Fontan circulation with increased PVR. These results suggest that ERAs might provide most pronounced hemodynamic and functional improvement in adults and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 25 publications
2
42
1
3
Order By: Relevance
“…Non‐pulsatile pulmonary flow has also been associated with the development of pulmonary vascular disease. Several studies have reported improvements in haemodynamics and functional capacity following the use of pulmonary vasomodulator therapy in Fontan patients; however, its use in this population is still controversial and the delineation of which Fontan patients would most benefit from these agents remains unclear. Despite the theoretical central role played by ventricular afterload in a single ventricle circulation, systemic vascular resistance (SVR) has not been well‐studied in this population.…”
Section: Introductioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Non‐pulsatile pulmonary flow has also been associated with the development of pulmonary vascular disease. Several studies have reported improvements in haemodynamics and functional capacity following the use of pulmonary vasomodulator therapy in Fontan patients; however, its use in this population is still controversial and the delineation of which Fontan patients would most benefit from these agents remains unclear. Despite the theoretical central role played by ventricular afterload in a single ventricle circulation, systemic vascular resistance (SVR) has not been well‐studied in this population.…”
Section: Introductioncontrasting
confidence: 71%
“…We have recently reported that, in association with low CI, even mild increases in PVRi portend a high risk of Fontan failure . Pulmonary vasomodulator therapy has been shown to increase functional capacity, cardiac output as well as reduce PVR in Fontan patients . Although more widespread use of these agents might have been hampered by the small effect size reported in some of these studies, the ideal candidate for its use is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…2426, 28, 29 A prospective study evaluated the effect of endothelin receptor antagonists in 24 Fontan patients with pulmonary vascular disease defined as PVRI>2 WU*m 2 25 . There was a significant drop in PVRI in all patients after 6 months therapy with bosentan or macitentan, and 70% of the patient had PVRI <2 WU*m 2 post therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients had concomitant increase in CI, and improvement in functional class and exercise capacity. 25 …”
Section: Discussionmentioning
confidence: 99%
“…18 On the contrary, 8 children and 8 adolescents with PVRI ≥2 WU*m 2 treated with bosentan had reduction of PVRI after 6 months of treatment. 19 Finally, a study of 6 Glenn and 12 Fontan patients showed improvement in pulmonary compliance and Nakata index of pulmonary artery size after treatment with sildenafil (n=1), bosentan (n=16), or ambrisentan (n=1). 20 As illustrated, much of the literature has focused on the Fontan population because earlier failure of single-ventricle palliation either after neonatal palliation (depending on the anatomy and amount of pulmonary blood flow after birth) or Glenn operation is more commonly related to ventricular dysfunction or other inherent patient risk factors.…”
Section: Failing Fontan Populationmentioning
confidence: 97%